Bibliodiversity of Small Academic Publishers: The Role of Open Access for Impact and Visibility - Cruz Romero, Roberto; Stephen, Dimity; Stahlschmidt, Stephan (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2025)
Large bibliographic databases highlight tangible and symbolic differences regarding the standards of quality attached to them, underlining diverging incentive structures for small and large academic publishers. To assess the academic differences associated with these, we explore bibliometric data for small publishers' journals from the Web of Science (WoS) and Scopus. We then discuss the visibility and impact of highly cited literature in small open access journals in relation to their cited references from indexed and non-indexed sources. We find that non-indexed references are consistently relevant for highly cited literature, yet the share of items that obtains high citation counts is rather small and uneven across disciplines. In general, we identify regional and linguistic specificities, whilst there are some observable thematic differences compared to more mainstream publications. In particular, we underline that a healthy bibliodiversity can, dependent on language or regional contexts, shape epistemic and scientific practices and narratives.